Здобувач вітчизняного ЗВО як потенційний споживач послуг воєнного туризму - Щука Галина; Shchuka Halyna; Scsuka Halina (ФОП Середняк Т.К., 2024)
Резюме. В статті проаналізовано результати опитування 288 здобувачів з 18 ЗВО України щодо їхнього ставлення до воєнного туризму. Встановлено перелік об’єктів та активностей у межах даного виду туризму, які їм цікаві. Визначено, на що потрібно звертати увагу, формуючи воєнні тури для молоді.

Abstract. The article analyzes the results of a survey of 288 recruits from 18 higher education institutions of Ukraine regarding their attitude to military tourism. A list of objects and activities within this type of tourism that are of interest to them has been established. It is determined what needs to be paid attention to when forming military tours for young people.
The recipient of a domestic institution of higher education as a potential consumer of military tourism services
Keywords: воєнний туризм; споживач воєнного туризму; послуги воєнного туризму